Physico-chemical and antimicrobial properties of essential oil extracted from lemongrass and patchouli using the supercritical carbon dioxide - Mith, Hasika (Animo Repository, 2006)
The essential oil of lemongrass (Cymbopogon citratus) and patchouli (Pogostemon cablin Benth) cultivated in the Philippines was obtained by supercritical carbon dioxide (SC-CO2) extraction. The raw materials of air-dried Lemongrass leaves and stems (100 grams) and Patchouli leaves (50 grams), was extracted in the range of temperatures of 35oC 50oC and pressures of 90 110 atm, at a constant flow rate of CO2 of 0.5m3/hr. The static extraction time was conducted for 40 minutes before the dynamic extraction to enhance the extraction yield. The oil yield from supercritical carbon dioxide extraction was potentially higher by 1.09% to 4.45% compared to that from steam distillation process. The physico-chemical properties of extract at constant temperature and highest pressure were determined. The pH of lemongrass and patchouli extract was revealed acidic with refractive index of 1.4827 and 1.5012, respectively. Moreover, lemongrass extract show a high specific gravity of 0.963 while patchouli is at 0.968. The acid and ester value of lemongrass is at 18.03 and 4.53 and patchouli is 18.32 and 5.71. Evaporation by exposure to outside room temperature was about 2 to 3.8 times faster than at room temperature. A wide range of chemical components from the extracts were identified through gas chromatography and mass spectrometry (GC/MS). The predominant components for lemongrass extract were citral (neral and geranial), myrcene, geraniol and linalool. In the case of patchouli extract, patchouli alcohol (patchoulol), bulnesene, guaiene, patchoulene and caryophellene have been found. The antimicrobial properties of both extracts were also investigated with microbiological tests against pathogenic strains of Gram-positive (Staphylococcus aureus, Bacillus subtilis), Gram-negative (Escherichia Coli, Pseudomonas aeruginosa) and fungi (Aspergillus niger, Saccharomyces cerevisiae, Candida albicans). The oils showed positively the different activities against these micro- ii - organisms with the various concentrations of 1000mg/ml, 100mg/ml, 10 mg/ml and 1 mg/ml. Key word: Supercritical Carbon Dioxide extraction, Lemongrass (Cymbopogon citratus), Patchouli (Pogostemon cablin), physico-chemical properties, antimicrobial activity.